The forgotten quantum pioneer who turned wartime spy. (15th November 2018) - Castelvecchi, Davide
Davide Castelvecchi enjoys the extraordinary life of Sam Goudsmit, the atomic sleuth nominated for a Nobel prize 48 times. Davide Castelvecchi enjoys the extraordinary life of Sam Goudsmit, the atomic sleuth nominated for a Nobel prize 48 times. Samuel Goudsmit gazes upwards whilst at a University of Michigan dinner. Emilio Segre Archives